PENGARUH EFEKTIVITAS MANAJEMEN DANA DESA TERHADAP PEMBANGUNAN EKONOMI MASYARAKAT (STUDI KASUS DI DESA KALIKAYEN) - Amanah Amanah; Ahwan Sholih (Prosiding Seminar Nasional Akuntansi dan Manajemen (SENAMA), 2018)
One of the government programs in supporting rural development is by issuing Village Funds as a source of village income. The Village Fund Allocation (ADD) provided, in principle, must adhere to the principles of accountability, transparency and participation and efficiency. This study examines the Village Fund in the Kalikayen region. The reason for taking the location is referring to previous research which says that Kalikayen Village is a village in which the village fund management is in accordance with the rules that apply in its management process. For this reason, the purpose of this study was to determine the relationship between Village Fund Management and the Economic Development Level of the Kalikayen Village Community. This analysis is carried out with a simple regression analysis method, with secondary data obtained from literature and primary data obtained from surveys, questionnaires and observations on the intended object. Statistical test results using SPSS, generated data that the R Square test results were found to be 0.181, this implies the meaning that the influence of village fund management variables on economic development variables is 18.1%. While the remaining 81.9% is explained by other unknown factors or variables in this study such as the enthusiasm of the residents, the leadership capacity of the village head, and others. Statistical test results prove that the village fund management variable (X) obtained sig value greater than 0.05 (0.114> 0.05). This means that the Hypothesis (Village Fund Management on Economic Development) which states that village fund management has a positive and significant effect on economic development is not accepted because to several factors including the village government is still focused on infrastructure development.